PENGARUH OWNERSHIP CONCENTRASION, RISK MANAGEMENT COMMITE, INTELLECTUAL CAPITAL DISCLOSURE TERHADAP ENTERPRISE RISK MANAGEMENT - teti rahmawati; Herma wiharno; Putri Amanda (Universitas Serang Raya, 2026)
The development of the banking world is increasingly rapid, giving rise to inter-company competence which aims to analyze and provide empirical evidence on the influence of ownership concentration, risk management committee and intellectual capital disclosure on enterprise risk management. The method used is a descriptive and verification method, with quantitative data types. The population of this research is the Annual Reports of Companies Listed on the Indonesia Stock Exchange (BEI). In 2018-2022, there were 47 companies or 235 data. Sampling technique uses Quota Sampling. So a sample of 42 companies or 210 data was determined. The results of this research show that ownership concentration, risk management committee, and intellectual capital disclosure have significant effect on enterprise risk management. ownership concentration, risk management committee, and intellectual capital disclosure Partially, it has a positive on enterprise risk management